EFFECTS OF LIMESTONE MINING ON ARABLE LANDS IN ASHAKA AREA, NIGERIA - Usman Hassan , Muhammad; Sadee, Abdulrasheed; Abubaka, Hauwa (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Mining has been linked to various environmental challenges such as land degradation, landslide, soil erosion and flooding. Land degradation is believed to be one of the major ways in which mining of minerals affects agricultural production in areas where such activities takes place. This study analysed the effects of limestone mining on arable lands in Ashaka Area, Funakaye Local Government, Gombe State where limestone is been mined by Ashaka Cement Plc (Lafarge). Data was generated using questionnaire, oral interviews and personal observations. Similarly, handheld GPS garmin76 was employed to establish the coordinates of the study area. A total of 94 respondents out of 100 sample size completed the survey questionnaire. Descriptive statistics was employed in the analysis and presentation of data. The study revealed that more than 90% of the respondent’s farmlands were seized by the mining activities. Other problems include: land degradation and pollution. According to the respondents quarry activities which continue to flourish in the study area have left behind some ponds and pits. They added that substantial farm lands have been lost due to mining activities. The Sudan vegetation was also denuded which left the quarried area vulnerable to erosion. In order to maximize the benefit of limestone mining and minimize the environmental effects there is need for an elaborate plan for sustainable quarry reclamation and conservation best practices using community participatory methods.